Fonctions et rôles des directeurs d'école : apports métaphoriques - Alain Guerrier (Nantes Université, 2013)
This research aims to reveal the logic and concepts of the leadership of Head teachers in the French primary education system. The French teachers were asked to specify their profession in metaphors and then interviewed to provide further clarification. Simultaneously the North American theory of leadership in education proposed by Spillane & al. is analysed and deconstructed to the same dynamic specification to enable comparison to the picture given in the research. The confrontation obtained permits the unveiling of conceptions profoundly rooted in the French system and to measure the differences in the optimisation proposed by the US research.